2018
DOI: 10.1051/matecconf/201819502004
|View full text |Cite
|
Sign up to set email alerts
|

Shear properties evaluation of natural fibre reinforced epoxy composites using V-notch shear test

Abstract: This paper discusses the results of an experimental investigation on the shear properties of natural fibre composites using the V-Notch or Iosipescu shear test. The natural fiber composites were made of jute and hemp fibers reinforced epoxy polymer resin. The testing was conducted using an MTS machine equipped with a 10 kN load cell in accordance with the ASTM standard D5379M. The testing machine was set-up to apply a load with a speed of 2 mm/min. It was found that the jute fiber composites (JFC) have an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Fajrin and co-workers [ 41 ] experimentally studied jute fibre–epoxy composites prepared by vacuum bagging process using Iosipescu shear testing (also in-plane shear); the jute fibre were provided in woven configurations. They reported a shear strength of 25.5 MPa and diagonal fractures known as off-axis failure mode.…”
Section: Resultsmentioning
confidence: 99%
“…Fajrin and co-workers [ 41 ] experimentally studied jute fibre–epoxy composites prepared by vacuum bagging process using Iosipescu shear testing (also in-plane shear); the jute fibre were provided in woven configurations. They reported a shear strength of 25.5 MPa and diagonal fractures known as off-axis failure mode.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 15 is shear failure mode and cracking pattern of chemically treated sisal fiber-reinforced concrete. Many researchers have been trying to study the shear strength of natural fibers using the V-notch (Iosipescu shear test) with the guidelines of ASTM standard D5379M [46]. From normal concrete (control mix), SFRC achieved higher shear strength with parallel trend lines.…”
Section: Split Tensile Strengthmentioning
confidence: 99%
“…An interfacial shear test was performed on jute/graphene composites by Sarker et al 65 and the strength obtained was 14.00 MPa, about 245% higher than the untreated jute fibres, which possessed a value of 4.16 MPa. Fajrin and Sari 103 studied the shear properties of jute and hemp fibre composites using the V-notch shear test and determined their strengths to be an average of 25.57 and 22.46 MPa, respectively. An interfacial shear test was also conducted on Noil hemp fibres by Etaati et al 70 and the value was found to increase to a maximum of 13.60 MPa when 5% of MAPP is added to a composite with 30% Noil hemp fibre content.…”
Section: Characterisationmentioning
confidence: 99%